2000
DOI: 10.1021/jp993441h
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Mechano-Catalysts for Overall Water Splitting

Abstract: Mechano-catalytic overall water splitting on Cu2O, NiO, and Co3O4 was investigated in order to reveal the reaction mechanism. The experimental results indicated that metallic elements of these oxides were generated during the reaction. Also, elemental metals Cu, Ni, and Co were oxidized into Cu2O, NiO, and Co3O4, respectively, when water was reduced into H2 by the metal powders under the same reaction condition. The metallic particles covered with the metal oxides evolved both O2 and H2. These results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 11 publications
0
33
2
Order By: Relevance
“…1 Cu 2 O powder is also a photocatalyst working under visible light irradiation; 2,3 however, the instance of the photocatalytic water splitting is unknown, although the edges of the conduction band and the valence band of Cu 2 O may be available for the water reactions to form H 2 and O 2 ͑Scheme 1͒. 4 According to photoelectrochemical studies on Cu 2 O, a few problems associated with water splitting have been indicated as follows: ͑i͒ when employing Cu 2 O as a photocathode, it often underwent reductive transformation, resulting in the formation of metallic Cu ͑Cu 0 ͒, because of the low activity of Cu 2 O for the reduction of water into H 2 , 4,5 and ͑ii͒ in a twoelectrode electrochemical cell system comprising a Cu 2 O photocathode and a Pt anode without bias, there was no confirmation of O 2 from water ͑at the Pt counter electrode͒, which may imply that the holes photogenerated at Cu 2 O ͑valence band͒ are not capable of water oxidation into O 2 .…”
mentioning
confidence: 99%
“…1 Cu 2 O powder is also a photocatalyst working under visible light irradiation; 2,3 however, the instance of the photocatalytic water splitting is unknown, although the edges of the conduction band and the valence band of Cu 2 O may be available for the water reactions to form H 2 and O 2 ͑Scheme 1͒. 4 According to photoelectrochemical studies on Cu 2 O, a few problems associated with water splitting have been indicated as follows: ͑i͒ when employing Cu 2 O as a photocathode, it often underwent reductive transformation, resulting in the formation of metallic Cu ͑Cu 0 ͒, because of the low activity of Cu 2 O for the reduction of water into H 2 , 4,5 and ͑ii͒ in a twoelectrode electrochemical cell system comprising a Cu 2 O photocathode and a Pt anode without bias, there was no confirmation of O 2 from water ͑at the Pt counter electrode͒, which may imply that the holes photogenerated at Cu 2 O ͑valence band͒ are not capable of water oxidation into O 2 .…”
mentioning
confidence: 99%
“…During the mechanocatalytic decomposition of water into H 2 and O 2 , the formation of reduced metal during the catalytic reaction was established by X-ray diffraction and chemical analysis; the authors of this research then concluded that a redox reaction between the metal and the metal oxide may be responsible for water splitting [31]. The mechanism for phenol decomposition should be different, since in our case it was not detected, by the X-ray diffraction analysis changes in the catalyst.…”
Section: Mechanism Of Phenol Degradation By Mechanical Activation Of mentioning
confidence: 68%
“…Besides, it has been shown that simple transition metal oxides, such as NiO, Co 3 O 4 , Fe 3 O 4 , and Cu 2 O, catalytically decompose distilled water into H 2 and O 2 during magnetic stirring in a glass reaction vessel at room temperature [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Hara et al [6] first reported the photocatalytic decomposition of water into H 2 and O 2 on Cu 2 O under visible light irradiation, but de Jongh et al [7] pointed out that Cu 2 O could be a promising material not just for direct photochemical water splitting but-in conjunction with a suitable redox system-as a p-type photoelectrode in an electrochemical photovoltaic cell. Later Hara et al [8] also observed the generation of metallic Cu during water splitting on Cu 2 O and proposed that a redox reaction between Cu and Cu 2 O may be responsible for H 2 and O 2 formation in the Cu 2 O-catalyzed overall water splitting. Cu 2 O nanocrystals have also been reported to be active in the photodegradation of various dye molecules under visible light illumination [10][11][12][13][14][15], but Shi et al [16] recently reported that Cu 2 O nanowire polyhedra only exhibited photocatalytic activity for dye photodegradation in the presence of H 2 O 2 under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the application of Cu 2 O crystal as photocatalyst in 949 water splitting and organic contamination degradation under visible light illumination has been explored [6][7][8][9][10][11][12][13][14][15][16], but these systems still need further investigation. Hara et al [6] first reported the photocatalytic decomposition of water into H 2 and O 2 on Cu 2 O under visible light irradiation, but de Jongh et al [7] pointed out that Cu 2 O could be a promising material not just for direct photochemical water splitting but-in conjunction with a suitable redox system-as a p-type photoelectrode in an electrochemical photovoltaic cell.…”
Section: Introductionmentioning
confidence: 99%